Faktor-faktor keberhasilan manajemen keuangan pribadi dengan gaya hidup sebagai pemoderasi - Dewi, Liana; Untung Eko Setyasari; Sinta Wulansari (Nur Science Institute, 2024)
Students are a generation capable of improving prosperity through good financial management. Unfortunately, many students still have financial management patterns that are far from expectations. Based on these problems, this research analyzes the factors that influence the success of personal financial management carried out by students. This research will involve lifestyle as a moderator of the relationship between the intention to carry out personal financial management and the implementation of students' personal financial management. The theory used in this research is planned behavior, a basic theory to understand the factors that cause students' low ability to carry out ideal personal financial management. This research is causal research with quantitative methods. The sample in this research consisted of students majoring in economics, accounting, and business. Data is collected through questionnaires that measure each variable and are tested based on the underlying theory. The research results show that the factors influencing personal financial management's success are attitudes, subjective norms, perceived behavioral control, and intentions. Lifestyle cannot moderate the relationship between students' intentions and behavior in managing personal finances.